Cross‐Cultural Differences in Sibling Power Balance and Its Concomitants Across Three Age Periods. Issue 156 (June 2017) - Buist, Kirsten L.; Metindogan, Aysegül; Coban, Selma; Watve, Sujala; Paranjpe, Analpa; Koot, Hans M.; van Lier, Pol; Branje, Susan J. T.; Meeus, Wim H. J.
Abstract: We examined cross‐cultural differences in (1) sibling power balance and (2) the associations between sibling power balance and internalizing and externalizing problems in three separate cross‐cultural studies (early childhood, late childhood, and adolescence). The early childhood samples consisted of 123 Turkish and 128 Dutch mothers (mean age for children was 4.9 years). In the late childhood samples, self‐report data were collected from 124 Indian and 129 Dutch children (mean age 10.9 years). In the adolescent samples self‐report data were collected from 165 ethnic Moroccan and 165 ethnic Dutch adolescents (mean age 15.2 years). In all studies, questionnaire data on sibling power imbalance and internalizing and externalizing problems were collected. Results showed only one significant cross‐cultural difference in sibling power imbalance: The Indian sample reported more sibling power imbalance than the Dutch. Links between sibling power imbalance and problem behavior were highly similar between the different cultural samples. The only significant difference was a stronger impact of sibling power imbalance on externalizing problems for the Dutch compared to the Turkish sample. Concluding, few cross‐cultural differences were found in sibling power imbalance. Across cultures and age groups, more sibling power imbalance was linked to more internalizing and externalizing problems.